Differences between DSM-IV and DSM-5 as applied to child and adolescent psychiatry and neurodevelopmental disorders. (29th September 2017) - Shujah, Z.; Mulligan, A.
Abstract : Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition ( DSM -5) was published by the American Psychiatric Association in 2013. We discuss the important differences between DSM -IV and DSM -5 with particular relevance to child and adolescent psychiatry. The DSM -5 diagnostic criteria for a diagnosis of autism spectrum disorder and of attention-deficit/hyperactivity disorder are discussed in detail, as well as a summary of other changes in DSM -5 relevant to child and adolescent psychiatry. The discussion is supported by a review of relevant literature.